Protective Effects of Inhibition of Mitochondrial Fission on Organ Function After Sepsis - Zhu, Yu; Kuang, Lei; Wu, Yue; Deng, Haoyue; She, Han; Zhou, Yuanqun; Zhang, Jie; Liu, Liangming; Li, Tao (Frontiers in Pharmacology, 2021)
Sepsis-associated organ dysfunction plays a critical role in its high mortality, mainly in connection with mitochondrial dysfunction. Whether the inhibition of mitochondrial fission is beneficial to sepsis-related organ dysfunction and underlying mechanisms are unknown. Cecal ligation and puncture induced sepsis in rats and dynamic related protein 1 knockout mice, lipopolysaccharide-treated vascular smooth muscle cells and cardiomyocytes, were used to explore the effects of inhibition of mitochondrial fission and specific mechanisms. Our study showed that mitochondrial fission inhibitor Mdivi-1 could antagonize sepsis-induced organ dysfunction including heart, vascular smooth muscle, liver, kidney, and intestinal functions, and prolonged animal survival. The further study showed that mitochondrial functions such as mitochondrial membrane potential, adenosine-triphosphate contents, reactive oxygen species, superoxide dismutase and malonaldehyde were recovered after Mdivi-1 administration via improving mitochondrial morphology. And sepsis-induced inflammation and apoptosis in heart and vascular smooth muscle were alleviated through inhibition of mitochondrial fission and mitochondrial function improvement. The parameter trends in lipopolysaccharide-stimulated cardiomyocyte and vascular smooth muscle cells were similar in vivo. Dynamic related protein 1 knockout preserved sepsis-induced organ dysfunction, and the animal survival was prolonged. Taken together, this finding provides a novel effective candidate therapy for severe sepsis/septic shock and other critical clinical diseases.